Gambaran Perilaku Vaksinasi COVID-19 pada Masyarakat Rural dan Urban di Kabupaten Serang - Fitria, Febriyeni; Alkaff, Raihana Nadra; Aristi, Dela; Bariyah, Aike Wella Bil; Rosyidah, Ainur; Salamah, Reni Ridatus (LPPM Hang Tuah Pekanbaru, 2024)
Public health status in Indonesia can be influenced by the implementation of healthy behavior in the community. There are differences in behavior between people in rural and urban areas and factors that can cause vaccine delays that have the potential to affect COVID-19 vaccination coverage in Indonesia. This study aims to determine the behavior of COVID-19 vaccination in rural and urban communities in Serang Regency. This study used a descriptive research design with a quantitative approach which was conducted in October−November 2021 with a sample of 334 people aged 18−59 years. The results showed that the vaccination status of the respondents was complete dose (rural 65.3% and urban 70.3%), waiting for dose 2 (rural 22.4% and urban 18.6%), and dose 1 had been received but the dosing schedule 2 had passed (rural 12.3% and urban 11.1%). Three perceptions that are still low in percentage are perceptions of vulnerability, perceptions of obstacles, and cues to act. Some of the reasons for stopping the termination of COVID-19 in the community are not yet feeling that they will have severe symptoms if exposed to COVID-19, feeling confused about information related to COVID-19, not being able to carry out COVID-19 vaccinations because the schedule for COVID-19 vaccination program coincides with other activities, did not receive an invitation from the local government to vaccinate against COVID-19, vaccinate because people in their environment had vaccinated against COVID-19, did not receive support from cadres or religious leaders for the COVID-19 vaccination. Improved policy behavior can be improved by changing perceptions of vulnerability to COVID-19, reducing barriers, and also providing cues according to education through social media with the key message of spending the full dose of vaccine.